The Gulf in the imagination: Migration, Malayalam cinema and regional identity - Ratheesh Radhakrishnan (Contributions to Indian Sociology (n.s.), 2009)
This article, taking up for analysis the three-decade-long relationship between the economy influenced by the Gulf and Malayalam cinema, in its industrial and narrative context, argues that the Gulf has been a significant point of reference for the imagining of a cultural identity in Kerala. It attempts to weave together three aspects—the development models that are in place, the economic conditions within which the film industry operates and the textual aspects of the films produced—to foreground the links between the economy, aesthetics and the imagining of regional identity. I argue that the contestation over regional identity was played out on aesthetic grounds, where the wealth and objects associated with the Gulf economy were deployed both at the formal and thematic levels, to produce claims about the legitimacy and desirability of the changes that become visible in the eco- nomic and social hierarchies within the region. The article examines the representations of the Gulf within the region, using select films from the commercial and art house cinemas of the 1970s, and middlebrow cinema of the 1980s and the turn of the century. These are read along with the economic changes within the film industry and the discourse of development in the region to mark the shifts that have happened to the desires and despairs associated with the Gulf dream.